Floor position in multitier broiler closed houses and its impact on microclimatic, air quality and litter conditions - Sarjana, T. A.; Mahfudz, L. D.; Suprijatna, E.; Sunarti, D.; Kismiati, S.; Muryani, R.; Binti Ma'rifah, B.; Shihah, H. D.; Wahyuni, N. M.; Istiqlali, S. B.; Saputra, T. I.; Ikhtiarita, R. N.; Adhiwangsa, R.; Qudsi, S.; Utomo, D. C. (Diponegoro University, 2024)
This study aimed to evaluate the effects of floor position in a multitier closed house on microcli-matic air quality and litter conditions. Fourteen thousand and five hundred unsexed Ross broiler chick-ens with a DOC body weight of 45.84 ± 2.40 g were placed on each floor of a three-tier closed house and allocated to a randomized block design consisted of 3 treatments and 18 replications. Each floor measured 12x78x2 m3. The maintenance procedure was applied according to the integrated partnership company guidelines PT Tumbuh Optimal Prima, with an observation period of 28 days. The treatments applied were as follows: T1= placement of broiler chickens on the 1st floor, T2= placement of broiler chickens on the 2nd floor, and T3= placement of broiler chickens on the 3rd floor. Microclimate condi-tions (temperature, RH, wind speed, temperature humidity index, wind chill effect, and calculated real feel temperature) and air quality parameters (NH3, CO2, O2, TVOC, and HCHO) were measured daily on each floor. Litter conditions, included water content, litter temperature, NH3 content, pH, and caking were measured weekly. The results revealed that during the starter phase (weeks 1–2), the microclimat-ic conditions and air quality of the 3rd floor were significantly better (P<0.05) than those of the 1st floor and 2nd floor, a trend was continued during weeks 3–4. Notably, the results obtained on the 1st and 2nd floors were still within the normal range for the broiler thermoneutral zone. Conversely, the 3rd floor litter was generally poorer, with significantly higher (P<0.05) moisture content, temperature, and cak-ing than the lower floors, particularly in weeks 3–4. However, broiler placement on different floors did not significantly affect the litter pH (P>0.05). In conclusion, the microclimatic conditions and air quali-ty of the 3rd floor were generally superior to those of the lower floors over the 4-week rearing period, whereas the litter quality was inferior.